Polymorphisms of the β2-Adrenergic Receptor Correlated to Nocturnal Asthma and the Response of Terbutaline Nebulizer - Ming-Yung Lee; Shin-Nan Cheng; Shyi-Jou Chen; Hui-Ling Huang; Chih-Chien Wang; Hueng-Chuen Fan (Pediatrics and Neonatology)
Inhaled β2-adrenergic receptor (β2-AR) agonists are the mainstay of treatment of acute asthma. Polymorphisms of the β2-AR, especially codons 16, 27, and 164, may affect the functions of the receptor. This study was conducted to investigate whether different polymorphisms of the β2-AR are related to the treatment responses of an inhaled β2-AR agonist in children with nocturnal and nonnocturnal asthma in Taiwan. Methods: The nocturnal asthma group consisted of 27 children (mean age of 10.3±2.4 years), and the nonnocturnal asthma group consisted of 24 patients (mean age of 9.9±3.0 years). Allele-specific polymerase chain reaction was performed to determine 16, 27, and 164 loci alleles of β2-AR genetic polymorphisms, and peak expiratory flow (PEF) was measured before and 1 hour after inhalation of 0.2 mg/kg/dose of terbutaline to determine the treatment response in these patients. Results: The polymorphisms of β2-AR 27 but not 16 or 164 were significantly associated with the response to terbutaline nebulizer (p<0.05). The polymorphism of β2-AR 16 was associated with nocturnal asthma (p=0.027). The Gly16 allele was more prevalent in the nocturnal asthma group (9/27; 33.3%) than in the nonnocturnal asthma group (3/24; 12.5%). Arg16 allele was less prevalent in the nocturnal asthma (3/27; 11.1%) than in the nonnocturnal asthma group (10/24; 41.7%). There was also a linkage disequilibrium found between β2-AR 16 (Arg/Arg) and β2-AR 27 (Gln/Gln). Conclusion: These findings suggest that polymorphisms of β2-AR 16 are related to nocturnal asthma and polymorphisms of β2-AR 27 are associated with the variable responses to the inhaled terbutaline in children with nocturnal and nonnocturnal asthma.